Kualitas Pelayanan Publik di Tingkat Kelurahan Parit Culum I Kecamatan Muara Sabak Barat - Dita Mei Diana; Citra Darminto; Fajar Alan Syahrier (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2026)
Public service is one of the main functions of government in fulfilling the administrative needs of society and realizing good governance. However, in its implementation, the quality of public services at the village level still faces various obstacles such as slow administrative processes, limited service facilities, and the lack of optimal utilization of information technology. This study aims to analyze the effectiveness of public services in Parit Culum I Village, Muara Sabak Barat District, and to identify the factors influencing the effectiveness of these services. This study employed a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The research informants consisted of the Village Head, Village Secretary, Head of Public Service/Government Section, and community members as service recipients. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the effectiveness of public services in Parit Culum I Village has generally been running quite well based on indicators of productivity, efficiency, quality, flexibility, and community satisfaction. Village officials were considered responsive and capable of providing administrative services according to community needs. However, public services have not been fully optimal due to obstacles such as the limited number of employees, inadequate service facilities, and the absence of an official website. Factors influencing the effectiveness of public services include the awareness of officials, service regulations, organizational factors, employee skills, income, and service facilities. This study implies that improving the quality of human resources, developing information technology-based services, and providing adequate facilities and infrastructure are essential to enhance the effectiveness of public services at the village level.